IMPROVING STUDENT’S MATHEMATICS LEARNING ACTIVITIES AND OUTCOMES USING MATHEMATICAL BAGATRIX AND POWER POINT SOFTWARE - Sudarsono, Andri; Supiyanto, Supiyanto; Batori, Batori; Hidayat, Teguh Imam Agus ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The purpose of this study is to analyze students’ mathematics learning activities and outcomes using mathematics instruction assisted by ICT mathematical Bagatrix software and PowerPoint. This study is a classroom action research in three cycles, on a linear equation of one variable (LEOV) and involves 20 seventh grade students of SMP Citra Cemara in Bandung.  The study found that students’ mathematics learning activities increased during each cycle, likewise, students’ mathematics learning outcomes and percentage of the number of students who reached mastering LEOV (more than 70% out of ideal score) heightened at end of each cycle. Another finding is that students perform positive opinion toward implementation of mathematics instruction assisted by ICT mathematical Bagatrix software and  PowerPoint.